FAGOTERAPIA: UNA ALTERNATIVA TERAPÉUTICA PROMETEDORA CUANDO LOS ANTIBIÓTICOS NO FUNCIONAN. - Astudillo Skliarova, Igor Eduardo (2023)
Introduction: For decades, phage therapy has been widely used to treat various infectious diseases. However, with the advent of antibiotics, its use declined. Nowadays, the resurgence of phage therapy serves as a reminder of its historical significance and a promising approach in the fight against antibiotic-resistant infections. Objective: To evaluate the efficacy of phage therapy in patients with infections caused by antibiotic-resistant bacteria. Methods: This bibliographic review adopts a descriptive approach, focusing on recent clinical cases where phage therapy was employed to treat infections caused by antibiotic-resistant bacteria. Clinical cases from the last five years available in the Pubmed database related to phage therapy were included as criteria. Results: A total of 59 clinical case reports that met the inclusion criteria were selected, and it was found that phage therapy demonstrated high efficacy in treating bacterial infections in patients with organ transplants, prosthetic and medical device infections, cystic fibrosis infections, and central nervous system infections. In some of these cases, phage therapy was used in combination with antibiotics, enhancing the effectiveness of the latter. Discussion: In all analyzed cases, phage therapy was shown to be a safe option, and in most instances, it proved to be highly effective. Furthermore, its ability to eradicate biofilms was evident, and in some cases, there was an improvement in the efficacy of antibiotics when used in combination with phages. Conclusions: The results of these studies demonstrate that phage therapy is an excellent alternative to antibiotics, particularly in the treatment of infections caused by antibiotic-resistant bacteria.